2022
DOI: 10.1371/journal.pbio.3001803
|View full text |Cite
|
Sign up to set email alerts
|

Differences in temporal processing speeds between the right and left auditory cortex reflect the strength of recurrent synaptic connectivity

Abstract: Brain asymmetry in the sensitivity to spectrotemporal modulation is an established functional feature that underlies the perception of speech and music. The left auditory cortex (ACx) is believed to specialize in processing fast temporal components of speech sounds, and the right ACx slower components. However, the circuit features and neural computations behind these lateralized spectrotemporal processes are poorly understood. To answer these mechanistic questions, we use mice, an animal model that captures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…All of this suggests a faster action potential transmission in the left auditory cortex, leading to a greater temporal resolution. This is confirmed in mice with reports of shorter temporal integration windows in left auditory superficial layers, a functional asymmetry associated with weaker recurrent excitatory synaptic connectivity (Neophytou et al, 2022) that results in different circuit-motifs (Levy et al, 2019).…”
Section: Introductionsupporting
confidence: 82%
“…All of this suggests a faster action potential transmission in the left auditory cortex, leading to a greater temporal resolution. This is confirmed in mice with reports of shorter temporal integration windows in left auditory superficial layers, a functional asymmetry associated with weaker recurrent excitatory synaptic connectivity (Neophytou et al, 2022) that results in different circuit-motifs (Levy et al, 2019).…”
Section: Introductionsupporting
confidence: 82%
“…Previous studies revealed an auditory pathway parcellation for temporal and spectral selectivity (i.e., Santoro et al, 2014). Hemispheric asymmetries were also observed (e.g., Flinker et al, 2019;Neophytou et al, 2022;Zatorre & Belin, 2001) with some studies suggesting left hemisphere sensitivity to temporal modulations and right hemisphere sensitivity to spectral content (Zatorre & Belin, 2001) and others suggesting greater left hemispheric selectivity for spectral modulations and weaker activations in the right hemisphere (Flinker et al, 2019). Contradictory findings likely stem from task and stimulus differences.…”
Section: Introductionmentioning
confidence: 90%
“…Other studies showed that the left hemisphere specialized in processing information at high temporal resolutions while the right hemisphere at slower temporal rates (Flinker et al, 2019). A recent study in the mouse model demonstrated that the activation of single neurons in the right auditory cortex persists longer than their homologue in the left hemisphere (Neophytou et al, 2022).…”
Section: Hemispheric Specialization Of Auditory Computations At High ...mentioning
confidence: 99%
“…Sound exposure during the auditory critical period selectively shapes Auditory Cortex (ACx) representations, whether for experimentally controlled tone pips or for the cadence of a child’s household language(s) 2-4 . In humans and mice, a fundamental feature of mature auditory sensory processing is the allocation of specialized cognitive functions to the Left and Right ACx 5-7 . Failure of the ACx to develop lateralized function is a common endophenotype of human cognitive disorders, such as Autism Spectrum Disorders and Schizophrenia 8,9 .…”
Section: Mainmentioning
confidence: 99%